KESEHATAN MENTAL MASYARAKAT: MENGELOLA KECEMASAN DI TENGAH PANDEMI COVID-19 - Deshinta Vibriyanti (Jurnal Kependudukan Indonesia, 2020)
The spread of the COVID-19 pandemic around the world not only has physical health impacts but also mental health. One of the effects of a pandemic on mental health that is feelings of anxiety about being exposed to viruses and the uncertainty of conditions during a pandemic. Anxiety needs to be managed properly so that it can still make alertness, but not excessive so that it causes worse mental health disorders. This paper aims to explain how to manage anxiety during a pandemic for the society with a literature study approach. From the perspective of social psychology, this paper concludes that managing anxiety at a proportional level, is the result of repeated perception of situations. The selection of information received during a pandemic is the key to managing anxiety. Next, adapt to the changes that occur so that can through a mentally healthy life in a pandemic.